Role competencies in interprofessional undergraduate education in complementary and integrative medicine: A Delphi study. (November 2020) - Homberg, Angelika; Klafke, Nadja; Glassen, Katharina; Loukanova, Svetla; Mahler, Cornelia
Highlights: Health professionals should be qualified for patient-centred care in undergraduate training programmes. Teaching the Expert role is central in interprofessional training on complementary medicine. The roles: Communicator, Professional and Collaborator have to be integrated in the Expert role. The Health Advocate and the Leader roles are less relevant in undergraduate training. Abstract: Objectives: Physicians and other health professionals like nurses, physiotherapists and midwives should be prepared to work in a patient-centred and team-based manner through appropriate interprofessional training. This includes consideration of patients' preferences for complementary treatment methods, as well as reflection of one's own professional role and that of the others. The CanMEDS Physician Competency Framework is an established instrument that describes the competencies of health professionals in seven roles. We investigated which role competencies should be addressed in an undergraduate interprofessional curriculum on Complementary and Integrative Medicine. Design: In a Delphi study, an interprofessional expert group evaluated the relevance of the CanMEDS role competencies (n = 49) and the respective individual competencies (n = 30) on a seven-point Likert scale. For analysis, we assigned the competencies according to the ratings, to four groups of relevance (consensus: >80 %) and compared the proportions of individual competencies classified as relevant within the seven role competencies. Results: The role Medical Expert was rated as highly relevant for all individual competencies. For the roles Professional, Collaborator, Communicator and Scholar, all or most individual competencies were rated at least as relevant. For the roles Leader or Health Advocate all individual competencies were rated as not relevant. Conclusions: In order to improve healthcare including complementary treatment options, it is initially of great importance to impart expert and communication skills in undergraduate interprofessional training in addition to improving teamwork. The acquisition of management and consulting skills could only be given priority in a later phase of training.